Le processus d'écriture et la maladie d'Alzheimer: Un état de l'art. Issue 2 (3rd April 2019) - Cadola, Liv; Marquis, Raymond; Champod, Christophe
Abstract: A document expert is often asked to evaluate the authenticity of writings. In a normal situation, the evaluation of the similarities and the discordances observed between a questioned sample and the reference material allows to support or infirm the hypothesis of authorship. However, when dealing with writing from aged people or people affected by a disease, the examination is more complex and natural variation can sometimes be confused with simulation's characteristics. It is the case with Alzheimer Disease (AD), a pathology that often develops in elderly and can change considerably, sometimes in a really short period of time, a person's handwriting. In those cases the expert can benefit from specific literature on the subject. Unfortunately, most of the papers are relevant to the medical fields and the impact of the disease on the writing process is presented in relation to a disruption at a particular writing process' level. In order to better understand the influence of AD on handwriting it is therefore fundamental to first understand the normal, healthy, process of text production. Once all the steps reviewed, it will be possible to decipher the impact of a deficit on a particular level on the resulting handwriting. This review aims at offering an overview of the influence of AD on handwriting by analyzing medical papers from a forensic point of view. This article is meant to help the document expert in cases where the questioned writing sample has been produced by a person affected by AD.